Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1136/bmjopen-2017-020061
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of plasma microRNA-122, high-mobility group box 1 and keratin-18 concentrations to stratify acute gallstone disease: a pilot observational cohort study in an emergency general surgery unit

Abstract: ObjectiveTo obtain pilot data to evaluate the discriminatory power of biomarkers microRNA-122 (miR-122), high-mobility group box 1 (HMGB1), full-length keratin-18 (flk-18) and caspase-cleaved keratin-18 (cck-18) in plasma to identify potential biliary complications that may require acute intervention.DesignAn observational biomarker cohort pilot study.SettingIn a Scottish University teaching hospital for 12 months beginning on 3 September 2014.ParticipantsBlood samples were collected from adults (≥16 years old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Cholecysto-choledocholithiasis may cause complications such as acute or chronic angiocholitis, obstructive jaundice, biliary pancreatitis, and liver function injury, or could be even fatal (5). Therefore, patients diagnosed with cholecystocholedocholithiasis should receive treatment immediately.…”
Section: ' Discussionmentioning
confidence: 99%
“…Cholecysto-choledocholithiasis may cause complications such as acute or chronic angiocholitis, obstructive jaundice, biliary pancreatitis, and liver function injury, or could be even fatal (5). Therefore, patients diagnosed with cholecystocholedocholithiasis should receive treatment immediately.…”
Section: ' Discussionmentioning
confidence: 99%
“…Joshi et al investigated 4 novel susceptibility loci ( SULT2A1 , TM4SF4 , GCKR , and CYP7A1 ) and confirmed one known locus ( ABCG8 ) of CG ( Joshi et al, 2016 ). Th’ng et al (2018) reported that plasma miR-122, ull-length keratin-18 (flk-18) and caspase-cleaved keratin-18 (cck-18) concentrations were increased in patients with gallstones compared with those without. In the present study, after the mouse model of CG was successfully constructed, 181 DE-mRNAs (including 104 up-regulated mRNAs and 77 down-regulated mRNAs) and 33 DE-lncRNAs (including 17 up-regulated lncRNAs and 16 down-regulated lncRNAs) between model and normal groups were screened.…”
Section: Discussionmentioning
confidence: 99%